المهارا ت القیادیة ودورها في تحقیق المیزة التنافسیة للمؤسسة المصرفیة: د راسة حالة بنك القرض الشعبي الجزائري لولایة تلمسان - aici, nabaouiia; oubekhti, nassira (Finance and Business Economies Review, 2017)
:The sector of public services said to be quiet different from the industrial one at different levels. It is, therefore, of crucial importance to investigate this area of interest in order to face the new phase of competition in the light of globalization where no clear borders are set and where also leadership is at the front of interest as one of the cornerstones of the success of any organization, whatever its field of work and is the cornerstone of any effort aimed at achieving success in the institutions, especially the banking institution. Our study is mainly concerned with the Algerian Popular Credit Bank To identify and demonstrate the role of leadership skills in the development and positive change in the bank, and haw to make it better through a set of procedures well appropriate and suitable to the market needs and thus achieve competitive advantage. The latter does not appear randomly, but results from the adoption of senior management of the banking institution a set of behaviors and practices emanating from the trends and strategies that help the banking institution to differentiate from its competitors, Especially that the variables of the current era impose on the banking institutions the need for distinguished leaders and the degree of competence and technical skill and knowledge and a high level of awareness and excellence to invest human energies and the absorption of technology to consolidate the values of work and the realization of responsibility towards society